Adubação de sistemas: nitrogênio em pastagem hibernal e cultivo de feijão em integração lavoura-pecuária - Rhoden, Anderson Clayton (2019)
The management of nitrogen fertilization and pasture height is fundamental for the success of the integrated crop-livestock system (ICLS). System fertilization is an important strategy to increase the efficiency of nutrient use as a function of the residual effect between crops. The objective was to evaluate the effect of nitrogen fertilization and grazing intensities on ammonium, nitrate and mineral N in the soil and bean nutritional status and yield in an ICLS. The experiment was conducted at the Pacheco farm, located in Abelardo Luz, SC, agricultural year 2016/2017, from the succession of two crops. In the winter of 2016, pasture phase, was conducted ryegrass cv. Winter Star kept under grazing by beef cattle, and in the grain crop phase, bean cv. IPR Tuiuiu. The experimental design was in randomized blocks with three replications, distributed in a factorial scheme (2x2). The first factor was nitrogen fertilization time, with nitrogen fertilization only in ryegrass pasture (N-Fert. Pasture), 200 kg of N ha-1, and fertilization only in grain crops, bean (N-Fert. Grains), 100 kg of N ha-1. The second factor was pasture height, regulated by means of continuous stocking and variable stocking rate, handled at high (25 cm) and low (10 cm) height. In the grain culture phase, one more factor was added, doses of N: zero; 50; 100 and 150 kg of N ha-1, in subplots allocated in all plots. The analyzed variables were ammonium, nitrate and mineral N in the soil at depths of 0-5; 5-10; 10-20; 20-40; 40-60 cm. Nitrogen fertilization of ryegrass and bean promotes an increase in ammonium, nitrate and mineral N content in the soil and does not cause losses of N by leaching of nitrate. The highest levels of ammonium, nitrate and mineral N in soil occurred in the N-Fert. Pasture, indicating that there is residual effect of pasture phase for the grain culture phase. The nutrients N and K present a dilution effect on bean. The dilution curve proposed by Lemaire and Salette (1984) for C3 plants was not adequate for the diagnosis of nitrogen nutritional status of bean. The management of the high height pasture promotes higher levels of ammonium in the soil and nitrogen nutrition index of the bean, indicating that the cultural remains are important in the N cycling. The productivity and accumulated DM of the bean were higher in the N-Fert. Pasture associated with nitrogen fertilization of bean. Bean productivity increased linearly with N doses in the N-Fert. Grains. The application of 150 kg of N ha-1 in the N-Fert. Grains resulted in bean productivity lower than zero dose in the N-Fert. Pasture.